Knowledge, beliefs, and practices about COVID-19 among students and the general public in Tamil Nadu: A cross-sectional study - Vajiravelu Suganthi; A Chandrabose; K C Subha; Sasikala Gunasekaran; Panneerselvam Periasamy (Apollo Medicine)
Objectives: The goals of this examination were to survey the information and data of the Coronavirus pandemic among the understudies and the overall population in Tamil Nadu (TN). Materials and Methods: A cross-sectional examination was completed among the understudies and in TN normal public in 2020. A cross-sectional examination was completed by poll apparatus circled through Google structures through web-based media, and information were dissected by Statistical Package Social Sciences Programming (SPSS) form 25, and the outcomes were analyzed utilizing investigation of difference (ANOVA) and Pearson's Chi-square test (χ2). Results: In general, 25.4% of the male and 74.46% of the female respondents showed great information, and practically, 36.25% showed moderate information. 56.43% of the members showed helpless information about COVID-19. The normal information score of understudies was 20.13%, which is viewed as inside the size of good information. Both the school of study and level of instruction fundamentally (P < 0.05) correlated with understudy information. Understudies who studied clinical sciences showed the most noteworthy 58.80% showing a decent information level. A large portion of the understudies utilized the web, television, and other web-based media and broad communications for social occasion data about COVID-19. Conclusion: The present study shows that the majority of students and the general public are aware of the current COVID-19 pandemic and are actively adopting preventative measures, which have stopped the illness from spreading to the next stage of the pandemic in the community.